Upravlenie fizicheskoi kul'tury i sporta v sisteme mestnogo samoypravleniya - Rasin, M. S. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Today by structural division of administration of city responsible for a condition and the development of physical culture and sports is the Department of physical culture and sports (earlier the department or the city committee on physical culture and sports). In modern socio-economic conditions the real necessity of preparation and contraction of the pact about joint activity, which will differentiate powers in the field of people's physical culture and sport. Thus, perfection of structure of an agency of management, arrangement of priorities in development of physical culture and sport in the city of Omsk from physical culture and improving the work in a lifeplace. To individual share in support of the highest sports have allowed in to realize in municipal education legislative bases of Russian Federation and to find ways of the effective decision the main task of the city's sport life.